2009
DOI: 10.3928/1081597x-20090814-04
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Six Cases of Advanced Ectasia After LASIK With 6-mm Intacs SK

Abstract: Within the scope of six cases with 9-month postoperative follow-up, implantation of 6-mm Intacs SK appears to be a safe and effective treatment option for management of advanced cases of keratectasia after LASIK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…However, disease progression can result in contact lens intolerance 23. After the introduction of the intrastromal corneal ring segment, Intacs (Addition Technology Inc., Des Plaines, IL, USA) in 2000 for KC,4 they has emerged as the mainstay of refractive management of contact lens intolerant keratoconic eyes with clear central corneas 311…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, disease progression can result in contact lens intolerance 23. After the introduction of the intrastromal corneal ring segment, Intacs (Addition Technology Inc., Des Plaines, IL, USA) in 2000 for KC,4 they has emerged as the mainstay of refractive management of contact lens intolerant keratoconic eyes with clear central corneas 311…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Intacs SK was introduced with two significant design modifications – a smaller inner diameter of 6.0 mm compared to 6.8 mm of the standard Intacs; and an elliptical cross-section compared to a hexagonal cross-section of the standard Intacs 11. Although the smaller diameter of Intacs SK was introduced to better address the higher refractive errors associated with the more severe forms of corneal ectasia, the smaller diameter of 6.0 mm with appropriate thickness also has a potential to achieve superior anatomical and refractive outcomes in the earlier stages of KC.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that inserting a single inferior INTAC in patients with post LASIK ectasia improves the BCVA and UCVA (4145). We have had a similar experience.…”
Section: Post Lasik Ectasiamentioning
confidence: 99%
“…Rodriguez et al . showed a clinically significant reduction in keratectasia with improvement in uncorrected visual acuity (UCVA), spherical equivalent and keratometry in patients with severe post-Lasik ectasia after placement of SK47…”
Section: Treatmentmentioning
confidence: 99%